Climate change impact on water resources in Indian river basins: A review - MANIVANNAN, S.; THILAGAM, V. KASTHURI; YALIGAR, RAVINDRA (Journal of Soil and Water Conservation, 2022)
Indian River basins are a source of water for 1.3 billion populations to fulfil the needs of all sectors. In recent years, there has been growing concern that the water resources of these river systems might impact global climate change, which might have severe consequences for the region’s human population. A larger number of studies have been reported on climate change’s impact on water resources. Still, there is a cavity in the interdisciplinary approach of the knowledge of climate change impacts on river basins of India. Hence, it is the right time to review the existing studies and identify future research areas for mitigating climate change impact on river basins. This review presents a clear picture of the studies on the impact of climate change on river basins, critical analysis, and suggested future thrust areas for research.